SARS-CoV-2 infection in children in Parma - Dodi, Icilio; Castellone, Eleonora; Pappalardo, Marco; Rubini, Monica; Veronese, Piero; Ruberto, Claudio; Bianchi, Laura; Iovane, Brunella; Maffini, Valentina (Acta Biomedica Atenei Parmensis, 2020)
not available